PENGGUNAAN ALIH KODE DAN CAMPUR KODE TERHADAP PELAJARAN BAHASA INDONESIA IMPLEMENTASI DARI UNDANG – UNDANG NO 24 TAHUN 2009 DI SMP GANESHA DENPASAR - Apriliani, Kadek (Sphota : Jurnal Linguistik dan Sastra, 2018)
CODE SWITCHING AND CODE MIXING TOWARDS INDONESIAN SUBJECT AS IMPLEMENTATION OF REGULATION NO. 24 YEAR OF 2009 IN SMP GANESHA DENPASAR ABSTRACT This research is aimed at analyzing the code switching and code mixing of the teacher and the students in the process of learning Indonesian in SMP Ganesha Denpasar. This research also describes the factors of code switching and code mixing of the teacher-students communication in the process of learning Indonesian in the class room. This research is a library research. The theoretical and referential material that is related to the research social situation is collected. The observation method is also done in order to analyze the response of the respondents. This method is done through the process of recording the phenomenon. Related to the research problem, the aims of this study is to analyze the types, the factors, and the influence of code switching and code mixing occurred in the process of learning Indonesian in SMP Ganesha Denpasar. This issue is related to the Indonesian regulation No. 24 Year of 2009. Keywords: code switching, code mixing, Indonesian